World-wide experience of pyridoxine use: experimental and clinical base for use in obstetric-gynecologic practice - O A Gromova; V N Serov; N V Kerimkulova; I U Torshin; O A Limanova; N V Nikiforova (IP Berlin A.V., 2013)
Various forms of vitamin В6 (pyridoxine, pyridoxal, pyridoxal phosphate) are endogenous co-factors of over 100 enzymes in human organism. The impact of pyrodoxine and other forms of vitamin В6 on such enzymes mediates the vitamin involvement in a wide range of metabolic processes. Vitamin В6 is also pharmacokinetic and pharmacodynamic magnesium synergist. Up to the present moment, the databases of scientific publications in biomedicine contain over 10000 studies in molecular, experimental and clinical effects of pyridoxine and other vitamers В6. In the present study, the systematic analysis of large set of publications was made on the basis of modern algorithms of search of scientific information. The available evidential base suggests that the use of pyridoxine products in combination with magnesium is prospective for support of liver function, preserved bone structure, reduced inflammation, oncoprotection, depression and premenstrual syndrome, as well as prophylaxis of diabetes and cardiovascular disorders. The studies have shown that pyridoxine is rather safe both in general and obstetric-gynecologic practice.